2006
DOI: 10.1002/gcc.20311
|View full text |Cite
|
Sign up to set email alerts
|

Three‐way translocation involves MLL, MLLT3, and a novel cell cycle control gene, FLJ10374, in the pathogenesis of acute myeloid leukemia with t(9;11;19)(p22;q23;p13.3)

Abstract: The MLL gene, at 11q23, undergoes chromosomal translocation with a large number of partner genes in both acute lymphoblastic and acute myeloid leukemia (AML). We report a novel t(9;11;19)(p22;q23;p13.3) disrupting MLL in an infant AML patient. The 5' end of MLL fused to chromosome 9 sequences on the der(11), whereas the 3' end was translocated to chromosome 19. We developed long-distance inverse-polymerase chain reaction assays to investigate the localization of the breakpoints on der(11) and der(19). We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Vieira et al (2006) identified all three fusion genes generated by a t(9;11;19)(p22;q23;p13.3) translocation [21]. The sole MLL-MLLT3 genomic fusion resulted in an in-frame transcript, as observed in the t(9;11) translocation.…”
Section: Discussionmentioning
confidence: 87%
“…Vieira et al (2006) identified all three fusion genes generated by a t(9;11;19)(p22;q23;p13.3) translocation [21]. The sole MLL-MLLT3 genomic fusion resulted in an in-frame transcript, as observed in the t(9;11) translocation.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 270 genes were found to be rearranged (Supporting Information Table 6), 47 of which are currently implicated in cancer (Supporting Information Table 7). This group includes genes previously associated with MF or Sézary Syndrome (SS) (ie, CDKN2A , CDKN2B , DLEU2 , KDM6A , TP53 , TP63 , and VAV1 ) and genes implicated in other hematological malignancies (eg, ARHGAP26 , CBFA2T3 , CHD2 , DOT1L , LCK , LPP , PBX1 , PTPN11 , MLLT3 , TAF15 , SPECC1 , ZMYM2 ) (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of studies performed in human cell lines ( Paulsen et al, 2009 ), we hypothesized that elevated R-loop levels are driving the accumulation of DNA damage in the splicing factor mutants. R-loops were examined specifically in the sf3b1 hi3394aTg mutants for two reasons: firstly, because Sf3b1 is a core component of the spliceosome and, secondly, because Ccdc94, Sfpq and Plrg1 also have splicing-independent cellular functions that could potentially complicate the analysis of R-loops in their respective mutant lines ( Mahajan, 2016 ; An et al, 2014 ; Shav-Tal and Zipori, 2002 ; Berry and Gould, 1997 ; Legerski, 2009 ; Vieira et al, 2006 ). To measure cellular R-loop levels, immunofluorescence was performed using the S9.6 monoclonal antibody, which recognizes RNA:DNA hybrid structures ( Boguslawski et al, 1986 ).…”
Section: Resultsmentioning
confidence: 99%